Digital Economy Transformation and ITS Impact on MSME Productivity in The Post-Pandemic Era - Syahputra, Danil; Syah, Syafrial (International Journal of Economics (IJEC), 2025)
The COVID-19 pandemic has fundamentally transformed the global economic landscape, accelerating digital adoption across all business sectors. In Indonesia, Micro, Small, and Medium Enterprises (MSMEs), which contribute 61.9% to the national GDP and employ 97% of the workforce, have undergone unprecedented digital transformation to survive and thrive in the post-pandemic era. This study aims to comprehensively analyze the impact of digital economy transformation on MSME productivity in Indonesia's post-pandemic landscape, examining both opportunities and challenges while providing strategic recommendations for sustainable growth. This research employs a qualitative methodology through systematic literature review and content analysis of 45 peer-reviewed articles, government reports, and international publications spanning 2020-2024. The study integrates Resource-Based View Theory, Technology Innovation Theory, and Transaction Cost Economics Theory to provide theoretical foundation. Digital transformation has demonstrated significant positive impact on MSME productivity, with studies showing productivity increases of up to 30% and profitability improvements averaging 35% through adoption of e-commerce platforms, digital marketing, and cloud-based management systems. However, challenges persist including limited digital literacy, inadequate infrastructure, and high implementation costs. While digital transformation presents substantial opportunities for MSME growth and competitiveness, successful implementation requires coordinated support from government, private sector, and educational institutions to address existing barriers and ensure inclusive digital economic development.